Factors Influencing the Intention to Make Donations Via Crowdfunding Platforms: A Case Study of Orangbaik.Id at LAZ Dompet Al-Qur’an - Cholifani, Tarisya (Islamic Economics and finance in Focus, 2026)
The development of digital crowdfunding platforms for collecting zakat, infaq, and alms (ZIS) presents significant opportunities, but utilization remains low, particularly on the orangbaik.id platform owned by LAZ Dompet Al-Quran, demonstrating a gap between the potential and realization of digital Islamic philanthropy. This study aims to analyze the influence of perceived usefulness, perceived ease of use, digital literacy, and religiosity on the intention to donate through the platform. The study used a quantitative approach with an explanatory research method, with 53 LAZ Dompet Al-Quran donors as subjects. Data were collected through questionnaires and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS. The results showed that perceived usefulness, perceived ease of use, and religiosity had a positive and significant influence on the intention to donate, while digital literacy had no significant influence. This finding confirms that the usability factor is the main determinant compared to ease of use, with the support of religiosity. The implications of this research provide theoretical contributions to the development of digital Islamic philanthropy literature as well as practical recommendations for zakat institutions in optimizing strategies to increase the use of the ZIS crowdfunding platform.